Reverse flow injection spectrophotometric determination of iron(III) using norfloxacin - Pojanagaroon T. (2014)
A reversed flow injection colorimetric procedure for determining iron(III) at the mug level was proposed. It is based on the reaction between iron(III) with norfloxacin (NRF) in 0.07 mol l(-1) ammonium sulfate solution, resulting in an intense yellow complex with a suitable absorption at 435 nm. Optimum conditions for determining iron(III) were investigated by univariate method. The method involved injection of a 150 mul of 0.04% w/v colorimetric reagent solution into a merged streams of sample and/or standard solution containing iron(III) and 0.07 mol l(-1) ammonium sulfate in sulfuric acid (pH 3.5) solution which was then passed through a single bead string reactor. Subsequently the absorbance as peak height was monitored at 435 nm. Beer's law obeyed over the range of 0.2-1.4 mug ml(-1) iron(III). The method has been applied to the determination of total iron in water samples digested with HNO(3)-H(2)O(2) (1:9 v/v). Detection limit (3sigma) was 0.01 mug ml(-1) the sample through of 86 h(-1) and the coefficient of variation of 1.77% (n=12) for 1 mug ml(-1) Fe(III) were achieved with the recovery of the spiked Fe(III) of 92.6-99.8%.